(untitled) (Olhar de Professor, 2021)
This paper elucidates the project Drawing in playful gestures, in which experiences of drawing were proposed to a group of children aged from 3 to 4 years old in a public school, considering the aesthetic dimension and the observation of the expressive process as organizers of the relationship between children and the cultural repertoire of art. This project is part of a research on teaching practices with the languages of the visual arts in Early Childhood Education. The purpose of the work is to present relations between approaches to drawing and pedagogical practices. It refers to the relationship between drawing, as a personal and cultivated gesture, and the mediation of the teacher, based on authors such as Barbosa (2010), Iavelberg (2006; 2013), Pillar (1996; 2012), Dewey (2010), Merleau-Ponty (1999) among others. It was evident that children were protagonists in the development of their expression in the language of drawing and that teachers might be partners in this process.